PROBLEMATIKA PENCARIAN INFORMASI KEISLAMAN GENERASI MUSLIM MILENIAL - Machsun Rifauddin; Arfin Nurma Halida (Nusantara Journal of Information and Library Studies (N-JILS), 2022)
Due to the different types of information and access to open Islamic literature, the millennial Islamic community is currently facing various challenges in finding information. This study aims to dig deeper into the problem of finding Islamic information for the millennial Muslim generation through literary studies from books, journals and academic papers. The result is that the problems faced by the millennial Muslim generation are the transition from printed information to digital, the domination of the Internet as a medium for searching for Islamic information in which radical Islamic literature exists. It shows that it is increasing due to open access through and publishers, bookstores, libraries. Low information literacy and anxiety are also barriers to seeking information. The role of the library is very important as information management, providing Islamic information in both printed and digital formats, and initiating open access.Keywords: Information search, Internet, Digital information, Islamic literature, Islamic libraryABSTRAKMasyarakat muslim milenial mengalami berbagai problematika dalam pencarian informasi pada masa ini karena jenis informasi yang beragam dan akses terhadap literatur keislaman yang terbuka. Penelitian ini bertujuan untuk meninjau problematika pencarian informasi keislaman bagi generasi muslim milenial secara lebih mendalam menggunakan kajian literatur baik dari buku, jurnal maupun artikel ilmiah. Hasil penelitian menunjukkan bahwa problematika yang dihadapi generasi muslim milenial terkait dengan pergeseran informasi cetak ke digital dan dominasi internet sebagai media pencarian informasi keislaman yang didalamnya terdapat literatur keislaman yang bermuatan radikal, juga akses yang semakin terbuka melalui penerbit, toko buku, dan perpustakaan. Kemampuan literasi informasi yang rendah dan kecemasan juga menjadi hambatan dalam melakukan pencarian informasi. Perpustakaan berperan penting dalam menyediakan informasi keislaman baik cetak maupun digital, membuka akses dan sebagai kontrol informasi.